(untitled) (Research, Society and Development, 2023)
This article analyzes data from Paebes 2021 and 2022 as a tool that can contribute to the teaching of Portuguese in Basic Education. For that, a statistical analysis was performed with the results of a State Public School in the North of the State of Espírito Santo in order to understand how the program produces and interprets its data for the evaluation results. Thus, we divided our analysis into the following items: participation, evaluation design and performance indicators - average proficiency and average performance standard, distribution of students by performance standard and percentage of correct answers per descriptor. The main results found in the analyzes of the 9th of Elementary School and 3rd of High School in 2021 and 2022, corroborate the field of school effectiveness and reiterate the significant and positive effect of external evaluations, showing that PAEBES comes as an important tool to identify possible weaknesses found in schools in Espírito Santo, as well as to point out ways for the elaboration and application of more assertive pedagogical interventions.